Evaluasi Kinerja Website Pelayanan Publik Pemerintah Daerah Pada Provinsi Kalimantan Timur - Lydia Indah Permatasari; Agus Munandar (Akuntansi dan Manajemen, 2022)
This research aims to evaluate the performance of websites managed by the regional government of East Kalimantan province and also to provide input on improving the performance of websites that are considered less good. There are 9 public service websites managed by the Government of East Kalimantan including the website of the flying pesut, SIPPD, website, si website, tepra website, foreign service travel website, cooperation database application website, grant website and bansos online, regional financial transparency website, performance report website. In this research the method used is an evaluation research method that is carried out by collecting data so that it can be compared with existing standards and will then be drawn conclusions. The data collection is done by observing and reviewinglibraries, and analyzing databy using web.dev to measure performance levels, accessibility, best practices and SEO. The results of this study showed that the performance of the website had a good assessment with the average overall website assessment of 73%. With the regular evaluation and improvements and improvements to public service websites owned by the East Kalimantan provincial government, more people are expected to be able to do so. You can use public service websites to get the information you need. The government needs to hold trainings to website managers so that they can support website management in order to be better and more qualified.